2004
DOI: 10.1021/om049536+
|View full text |Cite
|
Sign up to set email alerts
|

Self-Consistency versus “Best-Fit” Approaches in Understanding the Structure of Metal Nitrosyl Complexes

Abstract: The metal nitrosyl complexes RuX(CO)(NO)L 2 + (L ) P( t Bu) 2 Me, X ) F -, Cl -, BF 4 -, H 2 O, NCH, H -, no ligand, and CO) have been characterized by computing their structures, relative stabilities, and vibrational frequencies through Becke3LYP calculations on a RuX(CO)(NO)-(PH 3 ) 2 + model complex. In the case of X ) F -, Cl -, BF 4 -, and H 2 O, a square pyramidal (SP) geometry with a bent nitrosyl ligand is preferred. In the case of X ) NCH, H -, and CO two geometries exist as local minima: a trigonal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Wu et al examined the geometries of DNA oligomers and showed that the geometries of oligomers obtained by ONIOM-PCM were similar to those obtained by ONIOM calculations that included solvent effects by using an 8.0 Å water box . ONIOM-PCM is efficient for calculating energetics and geometries for chemical reactions in which solvent molecules do not participate in the reaction explicitly. ,,, The properties of excited states, such as absorption and emission spectra, are sensitive to the change of charge distribution by surroundings. Thus, the consideration of polarizability of solvent is essential for such calculations (see section ) .…”
Section: Applications To Solution Chemistrymentioning
confidence: 93%
See 2 more Smart Citations
“…Wu et al examined the geometries of DNA oligomers and showed that the geometries of oligomers obtained by ONIOM-PCM were similar to those obtained by ONIOM calculations that included solvent effects by using an 8.0 Å water box . ONIOM-PCM is efficient for calculating energetics and geometries for chemical reactions in which solvent molecules do not participate in the reaction explicitly. ,,, The properties of excited states, such as absorption and emission spectra, are sensitive to the change of charge distribution by surroundings. Thus, the consideration of polarizability of solvent is essential for such calculations (see section ) .…”
Section: Applications To Solution Chemistrymentioning
confidence: 93%
“…591 ONIOM-PCM is efficient for calculating energetics and geometries for chemical reactions in which solvent molecules do not participate in the reaction explicit- ly. 204a, 287,330,592 The properties of excited states, such as absorption and emission spectra, are sensitive to the change of charge distribution by surroundings. Thus, the consideration of polarizability of solvent is essential for such calculations (see section 7).…”
Section: Four Oniom-pcm Treatments and Theirmentioning
confidence: 99%
See 1 more Smart Citation
“…9,12 A further complication is the limited ability to correlate calculated electronic structures and M−N−O bond angles with IR data. 13 As such, electronic structure characterization of M− NO species generally involves significant spectroscopic and computational efforts. angle is especially important in enzymes such as the reduced forms of nitrite reductase (NiR) that exhibit side-on NO bonding.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Infrared spectroscopy (IR) is generally used to characterize the presence of a metal nitrosyl, and the IR stretch is sensitive to NO activation/NO bond length and the metal–N–O bond angle. The contributions from activation and bond angle, however, are difficult to deconvolute and not well-quantified. , A further complication is the limited ability to correlate calculated electronic structures and M–N–O bond angles with IR data . As such, electronic structure characterization of M–NO species generally involves significant spectroscopic and computational efforts.…”
Section: Introductionmentioning
confidence: 99%